Proteomic and Functional Signatures of Phenoconversion in Presymptomatic Amyotrophic Lateral Sclerosis - Steven Lehrer; Peter H. Rheinstein (Journal of Clinical Neuromuscular Disease, 2026)
Background: Amyotrophic lateral sclerosis (ALS) likely has a prolonged presymptomatic phase. Identifying blood biomarkers that predict phenoconversion is critical for early intervention. Methods: We analyzed baseline serum proteomics in 270 UK Biobank participants who later developed ALS. A prespecified 19-protein panel was evaluated in relation to time-to-diagnosis. C9orf72 risk was proxied using rs10757668 genotype. Results: Neurofilament light rose sharply in the 2–3 years preceding diagnosis ( r = −0.37, P < 0.001). Muscle-stress markers, including EDA2R and MYL3, increased earlier, up to 4–6 years before onset. Higher EDA2R levels were associated with reduced grip strength at baseline. A combined 19-protein panel plus genotype predicted phenoconversion within 3 years with an area under the receiver operating characteristic curve of 0.77, outperforming neurofilament light alone. Conclusions: ALS exhibits a measurable molecular prodrome detectable in blood years before diagnosis. Integrated proteomic and genetic profiling may support early identification and trial enrichment strategies.